Sustainable Development of World Tourism Based on the Strategic Management - Parfinenko, Anatoliy; Sokolenko, Liudmyla; Bielialov, Taliat; Karpenko, Nina G.; Парфіненко, Анатолій Юрійович; Соколенко, Людмила Федорівна; Бєлялов, Талят Енверович; Карпенко, Ніна Григорівна; Vitaliy Tolubyak; Толуб'як, Віталій Семенович (Allied Business Academies (London), 2019)
The article deals with the issues of ensuring the dynamic sustainable development of the world tourism industry based on strategic management approaches. The modern strategic models of development of the world tourism industry are set aside and analytically substantiated. An algorithmic model of selecting the best strategy for travel companies has been created, taking into account the factor of strengthening international strategic positions. The methodological structure of the study will be based on empirical studies showing that political and socio-economic instability ambiguously influences the trends of world tourism development. In the current conditions of informatization, globalization of economy, hypercompetition it becomes obvious that an important factor of operation of tourism system is its provision with adequate model of development. We define strategic management as one of the leading approaches to management in the context of universal dynamism, unpredictability and volatility of the business environment. The application of the concept of strategic management in the sphere of world tourism should only take into account the specific activity of the tourist company, interests of consumers of tourist services, existing conditions of competition and principles of sustainable development. The concept of sustainable world tourism can solve two problems: 1) the need for balanced development of the tourism industry; 2) considers limitations on existing natural resources and their conservation and multiplication for future generations.
Keywords: Strategic Management; Strategic Positions; World Tourism; Travel Company; World Tourism Industry Development Model